2016
DOI: 10.1093/sleep/zsw034
|View full text |Cite
|
Sign up to set email alerts
|

Dual Orexin Receptor Antagonist, Almorexant, in Elderly Patients With Primary Insomnia: A Randomized, Controlled Study

Abstract: Two-night oral administration of almorexant was effective and well tolerated in treating primary insomnia in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The initial proof‐of‐concept that ORAs might be effective treatments for insomnia was established with the DORA almorexant/ACT‐078573 (Brisbare‐Roch et al., ; Hoever et al., ). Published results show generally similar findings to those described above for suvorexant (Black et al., ; Hoever et al., ; Roth et al., ). Development of almorexant was discontinued due to infrequent transient increases in liver enzymes unrelated to the orexin mechanism (Hoch, Van Gorsel, Van Gerven, & Dingemanse, ).…”
Section: Other Oras Investigated and Doras Versus Sorassupporting
confidence: 87%
“…The initial proof‐of‐concept that ORAs might be effective treatments for insomnia was established with the DORA almorexant/ACT‐078573 (Brisbare‐Roch et al., ; Hoever et al., ). Published results show generally similar findings to those described above for suvorexant (Black et al., ; Hoever et al., ; Roth et al., ). Development of almorexant was discontinued due to infrequent transient increases in liver enzymes unrelated to the orexin mechanism (Hoch, Van Gorsel, Van Gerven, & Dingemanse, ).…”
Section: Other Oras Investigated and Doras Versus Sorassupporting
confidence: 87%
“…Importantly, these findings have strong implications for various sleep-related conditions such as insomnia characterized by bouts of wakefulness after sleep onset (WASO) [47]. Indeed, Suvorexant and Almorexant are effective to decrease bouts of wakefulness in patients with insomnia characterized by WASO [30,43] and the data presented here suggest that this may be a result of its effects on specific sleep features such as increasing NREM sleep and the intrusion of NREM sleep into wakefulness.…”
Section: Discussionmentioning
confidence: 62%
“…Multiple lines of study have examined the effect of selective or dual OX1R and OX2R antagonism on sleep modulation [19][20][21][22][23][24][25][26][27][28][29]. ACT-078573 (Almorexant), a dual OX1/2R antagonist, has been shown to be effective in treatment of primary insomnia in humans [30], and has been shown to increase both non-rapid eye movement (NREM) and rapid eye movement (REM) sleep as measured by electroencephalogram (EEG) and electromyography (EMG) or behavioral changes, in rats, canines, and humans [19]. Suvorexant, a dual OX1/2R antagonist is effective in decreasing sleep latency, and has comparable EEG spectral profiles to normal sleep [20,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In one example, Falkenstein et al [7] demonstrated that patients achieved better VA when using the Early Treatment Diabetic Retinopathy Study (ETDRS) chart, which has a background luminance of 121.0 cd/m 2 , than when using the standard Snellen chart, which has a background luminance of 65.0 cd/m 2 . Similarly, our prior study found that near VA was approximately 1 line better when measured on a back-illuminated electronic device than when measured on an equivalent Rosenbaum near vision card [8]. As a result, back-illumination may be one strategy for improving VA and reading performance.…”
Section: Introductionmentioning
confidence: 77%
“…The advantage of back-illumination was even more pronounced in participants with lower VA (Table 2, Figure 1). Given that reading performance has been shown to be a function of multiple visual parameters such as VA, contrast sensitivity, and fixation stability, this improvement in reading speed may, in part, be due to the ability of back-illuminated devices to enhance text contrast and VA, especially in those with impaired visual function [35, 8]. …”
Section: Discussionmentioning
confidence: 99%